Pertumbuhan dan Sintasan Ikan Bandeng (Chanos chanos Forsskal) yang Diberi Pakan dengan Dua Jenis Sumber Bahan Baku Karbohidrat Pakan yang Terhidrolisis Limbah Cairan Rumen Sapi - Andi Masriah; Alpiani Alpiani (Universitas Gorontalo, 2019)
Feed which is one of the most important factors in increasing fish growth must have good nutritional quality, meanwhile there is a problem of production efficiency in aquaculture, especially in intensive aquaculture caused by high feed costs due to high protein requirements. The effort to reduce the role of protein as a source of energy in feed is to maximize the use of feed carbohydrates as an energy source. This study aims to determine the type of carbohydrate raw material that is most effectively hydrolyzed by cow's rumen liquid waste and determine the type of feed carbohydrate raw material that is effective after being fed beef rumen fluid to maximize growth and survival in milkfish. The method in this study uses a completely randomized design (CRD) consisting of 3 treatments, namely (a) control using commercial feed; (b) feed with carbohydrate as a source of flour; and (c) feed with the source of raw material carbohydrate refined bran flour. The growth and survival data obtained were analyzed by variance analysis (ANOVA) and continued with the W-Tuckey test. The results of the analysis showed that feeding with various types of carbohydrate sources in the feed which was fermented first using cow's rumen liquid waste significantly affected (P <0.05) on the growth and survival of milkfish. Feeding with carbohydrate sources both wheat flour and fine bran which is fermented first by using cow rumen liquid waste provides growth and survival in milkfish which is better than the use of commercial feed.